Korelasi Pengetahuan dan Minat Donor Darah pada Remaja di MA Hidayatullah Martapura - Yolanda, Devina (HB PRESS, 2024)
High school adolescents on the risks of unsafe blood donation and the benefits of safe blood donation practices. Adolescents can be effective as youth cadres in promoting public awareness about voluntary blood donation due to their active nature, curiosity, and social responsibility. The study uses an observational analytic design with a cross-sectional approach and involved 122 students from MA Hidayatullah Martapura. Data was gathered through a questionnaire, analyzed using SPSS. Findings reveal that 22.8% of respondents have a low level of knowledge about blood donation, mainly due to limited awareness of its health benefits and lack of information access through media channels. A significant positive correlation was found between knowledge and interest in blood donation (sig 0.001 < 0.05) with a moderate correlation strength (Pearson value 0.431). Additionally, 52.7% of students possess sufficient knowledge about blood donation, and 65.7% demonstrate an interest in participating as blood donors. These results highlight the importance of providing adolescents with relevant information to boost their awareness and engagement in safe blood donation practices.